Exact conic section arc elements in 2D and 2.5D FEM using a coordinate transformation. Issue 9 (5th April 2021) - Codecasa, Lorenzo; Gentili, Gian Guido; Khosronejad, Misagh; Pelosi, Giuseppe; Selleri, Stefano
Abstract: This study introduces the conic section arc elements in 2D and 2.5D finite element method (FEM). Elements are obtained by deforming an edge in a standard triangular element through a coordinate transformation. This allows to completely eliminate the geometrical error in structures composed of circular, elliptical, hyperbolic and parabolic arcs. The element order is defined independently of the geometrical description of the boundary, allowing the use of simple meshers. Previously available FEM codes can be straightforwardly modified to introduce the conic section boundaries.